2022
DOI: 10.1161/jaha.122.027573
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D1 Regulates Cardiac Hypertrophy, Potassium Channel Remodeling, and Arrhythmias in Heart Failure

Abstract: Background Structural and electrophysiological remodeling characterize heart failure (HF) enhancing arrhythmias. PKD1 (protein kinase D1) is upregulated in HF and mediates pathological hypertrophic signaling, but its role in K+ channel remodeling and arrhythmogenesis in HF is unknown. Methods and Results We performed echocardiography, electrophysiology, and expression analysis in wild‐type and PKD1 cardiomyocyte‐specific knockout (cKO) mice following tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Hypertrophy is a compensatory response to HF, but sustained cardiac hypertrophy contributes to the development of HF. Remodeling in I Kr and I Ks in HF have also been reported (57)(58)(59). A study conducted in rabbits with atrioventricular block showed a reduction of both I Kr and I Ks , using the patch-clamp technique (60,61).…”
Section: Potassium Currentmentioning
confidence: 89%
“…Hypertrophy is a compensatory response to HF, but sustained cardiac hypertrophy contributes to the development of HF. Remodeling in I Kr and I Ks in HF have also been reported (57)(58)(59). A study conducted in rabbits with atrioventricular block showed a reduction of both I Kr and I Ks , using the patch-clamp technique (60,61).…”
Section: Potassium Currentmentioning
confidence: 89%
“… 35 This was associated with restoration of protein kinase D1 function, 35 which importantly regulates cardiac hypertrophy and progression to heart failure with reduced EF. 36 Aldosterone infusion alone induces mild changes in cardiac function unless accompanied by additional stressors (eg, uninephrectomy+salt water 21 or myocardial infarction). 37 Here we showed that combined db/db +Aldo synergistically induces marked diastolic dysfunction, concentric cardiac hypertrophy, pulmonary congestion, and multiple common comorbidities of HFpEF, including diabetes, obesity, and increased vascular resistance (Figures 1 , 2 , 3 ), more closely recapitulating important aspects of human HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…PRKD is also associated with the phosphorylation of the sarcomeric protein cardiac troponin I (Cuello et al., 2007 ; Haworth et al., 2004 ; Martin‐Garrido et al., 2018 ), indicating that it is a regulator of cardiomyocyte contraction. Further, PRKD1 is known to regulate pathologic cardiac hypertrophy through its action on class II histone deacetylases (HDACs) and signalling via the myocyte enhancer factor‐2 family (MEF2) and TBX5 (Fielitz et al., 2008 ; Ghosh et al., 2009 , 2019 ; Kim et al., 2008 ; Vega et al., 2004 ), and plays a role in the subsequent K + channel remodelling with the potential to cause arrhythmia (Bossuyt et al., 2022 ). It also plays a role in VEGFA‐induced angiogenesis (Di Blasio et al., 2010 ; Wang et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%